RESEARCH OF THE EFFICIENCY OF THE APRIORI GROUP ALGORITHMS ON DIFFERENT DATABASE SIZES - Половинка, Ольга; Дмитриева, Ольга (SWorldJournal, 2020)
The results of the work analysis of associative rule search algorithms for handling Big data are presented in the paper. The most famous modifica-tions of Apriori algorithms for finding associative rules are considered. The re-sults of the research of th